Transborder logistics network design for agricultural product transportation in the Greater Mekong Subregion - Natthapong Nanthasamroeng; Surajet Khonjun; Thanatkij Srichok; Rapeepan Pitakaso; Raknoi Akkararungroeungkul; Ganokgarn Jirasirilerd; Sarinya Sirisan (Asian Journal of Shipping and Logistics, 2022)
This research aimed to design a transportation model for the international trade of agricultural products between Thailand, Laos, and Cambodia, known as the Great Mekong Subregion (GMS). Agricultural products are transported from a farmers’ cooperative to a foreign end market. The mathematical models GA, DE, and VaNSAS were developed to determine the optimal mode of transportation. The objectives of the proposed methods are to (1) maximize the total profit for the entire agricultural chain and (2) minimize the makespan or the arrival time of the containers to the end market in order to maintain the freshness of the agricultural product. The computational result shows that VaNSAS produces a 100 % optimal solution for small-size problem instances, while DE and GA produce a 63.63 % and 72.72 % optimal solution, respectively. For large-size problem instances, VaNSAS shows a profit that is higher than that of DE and GA by 10.53 % and 8.96 %, respectively, while it shows a makespan that is lower by 9.57 % and 7.20 %, respectively.